O brincar e a teatralidade no contexto da educação infantil:: uma proposta pedagógica (Revista NUPEART, 2021)
This essay discusses education and art and artistic intentions in relation to early childhood education. The difficulties of a teacher are narrated when venturing into an artistic proposal with her students / preschoolers and also the emancipatory processes from which a new vision of art and children emerged. In this sense, the essay demonstrates the importance of having a “common object” between the teacher and her small students, in this case, play. It also demonstrates the importance of working the theater in a playful way, presenting a path to theatricality. In addition, the play trail is illustrated by images by the plastic artist Dim Brinquedim. The text makes a dialogue between reading and theoretical reflection with the experience of a public-school teacher, highlighting its particularities: events, desires, dreams and sensations that school and art provide.
Keywords: Childhood Education. Play. Theatricality